Ammonia gas adsorption material based on bimetallic MOF / resin and preparation method of ammonia gas adsorption material
By introducing Cu/Co bimetallic MOF in the resin synthesis process of ammonia adsorbent materials, the composite adsorbent materials are formed, which solves the problems of low efficiency and environmental risks of existing materials when removing ammonia, and achieves an efficient and low-cost ammonia removal effect.
Patent Information
- Application Number
- CN202411770181.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
AI Technical Summary
Existing ammonia adsorbent materials such as activated carbon and acid ion exchange resins have problems such as blockage of pore structure, low removal efficiency, and environmental and health risks when removing ammonia.
A composite material of Cu/Co bimetallic MOF and polystyrene sulfonated resin is used to introduce MOF-based materials during the resin synthesis process to form a composite adsorption material with bimetallic MOF as the core, thereby increasing the specific surface area and active sites.
It significantly improves the removal efficiency of ammonia, reduces the preparation cost and cycle, and avoids the risks brought by traditional impregnation modification, and is suitable for industrial applications.
Smart Images

Figure BDA0005170072270000051 
Figure HDA0005170072280000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorption materials, and in particular relates to an ammonia adsorption material based on bimetallic MOF / resin and a preparation method thereof. Background Art
[0002] The sources of ammonia include agriculture (fertilizer production), manufacturing (such as ammonia and coke production), sewage treatment plants and refrigeration systems. Ammonia has certain harm to human physiology, and can form photochemical smog and cause eutrophication of surface water, which affects the environment; effective removal of ammonia is necessary.
[0003] There are many materials to choose from for the removal of ammonia, but most of the research is still focused on porous materials such as activated carbon. Activated carbon is an excellent carrier that can load a lot of impregnation liquid through simple impregnation, and the impregnation liquid can remove ammonia by coordination and complexation with ammonia. For example, patent CN109692662A discloses an ammonia adsorbent, which uses activated carbon as a carrier, impregnates an ethanol solution of transition metal oxides, and then burns the filtered activated carbon to obtain modified activated carbon with excellent ammonia absorption performance. Patent CN104368307A discloses a special activated carbon for ammonia adsorption, which uses commercial activated carbon as raw material, and obtains an activated carbon material that efficiently adsorbs ammonia through processes such as acidification, inorganic salt impregnation, washing, filtering, and drying. Although impregnation is a simple and low-cost modification process, metal salt impregnation modification is easy to precipitate on the surface of activated carbon, causing blockage of the activated carbon pore structure, reducing the porosity, and thus reducing the ammonia removal efficiency; in addition, the precipitation and shedding of these transition metal salts and metal oxides will bring many uncertain risks to the environment and health.
[0004] Acidic ion exchange resins can be used to remove ammonia nitrogen from water, and can be used to adsorb ammonia. However, ion exchange resins have the following two limitations: low specific surface area, which affects the absorption rate of ammonia; and fewer active sites, resulting in a low total amount of ammonia adsorbed. Summary of the invention
[0005] The main purpose of the present invention is to provide a polystyrene sulfonated resin composite adsorption material containing Cu / Co bimetallic MOF in view of the problems and shortcomings of the prior art. The introduction of MOF-based materials during the resin synthesis process can accelerate the resin synthesis process and promote the effective loading of the bimetallic MOF in the resin. The obtained composite adsorption material has a high specific surface area and active sites, and has a high removal efficiency for ammonia. The preparation cost involved is low and the cycle is short, which is suitable for promotion and application.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An ammonia adsorption material based on bimetallic MOF / resin, the preparation method of which comprises the following steps:
[0008] 1) adding styrene sulfonate, an initiator and a Cu / Co bimetallic MOF material to water, and ultrasonically dispersing the mixture to obtain an aqueous phase solution; and uniformly stirring the vinyl monomer and the liquid porogen to obtain an organic phase solution;
[0009] 2) The aqueous phase solution and the organic phase solution are mixed, and heated and polymerized under stirring conditions, and the liquid porogen is removed to obtain porous microspheres, which are protonated to obtain the bimetallic MOF / resin-based ammonia adsorption material.
[0010] In the above scheme, the preparation steps of the Cu / Co bimetallic MOF material include: uniformly dispersing copper salt, cobalt salt and organic ligand in a mixed solvent, then heating reaction, cooling, filtering, washing and drying to obtain the Cu / Co bimetallic MOF material.
[0011] In the above scheme, the step of removing the liquid porogen in step 2) includes: after heating the polymerization reaction, filtering, washing, and then performing Soxhlet extraction to remove the liquid porogen.
[0012] In the above scheme, the copper salt can be selected from one or more of copper nitrate, copper chloride, copper sulfate, copper acetate, copper phosphate, etc.; the cobalt salt can be selected from one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt phosphate, etc.
[0013] In the above scheme, the organic ligand can be selected from one or more of trimesic acid (H3BTC), DMF, EtOH, EDA, DMSO and the like.
[0014] In the above scheme, the molar ratio of the copper salt, the cobalt salt and the organic ligand is 1:0.5-2:1-4.
[0015] In the above scheme, the mixed solvent comprises ethanol, DMF and water.
[0016] Furthermore, in the mixed solvent, the volume ratio of ethanol, DMF and water is 1:0.5-2:0.5-2.
[0017] In the above scheme, the ultrasonic time in step 1) is 5-60 min.
[0018] In the above scheme, the heating reaction step in step 1) includes: heating to 50-150° C., keeping the temperature for 1-72 hours and then naturally cooling to room temperature.
[0019] In the above scheme, the styrene sulfonate can be selected from one or more of sodium styrene sulfonate, 2-(styrenesulfonyl)acetic acid, sodium p-styrene sulfonate, sodium β-styrene sulfonate and the like.
[0020] In the above scheme, the initiator can be selected from one or more of azobisisopropionitrile, benzoyl peroxide, persulfate and the like.
[0021] In the above scheme, the mass ratio of the styrene sulfonate, the initiator and the Cu / Co bimetallic MOF material is 1:0.05-0.4:0.01-0.10.
[0022] In the above scheme, the ultrasonic dispersion time in step 2) is 5-120 min.
[0023] In the above scheme, the liquid porogen can be selected from one or more of toluene, cyclohexane, n-heptane, linear polystyrene, petroleum ether, dibutyl phthalate and the like.
[0024] In the above scheme, the vinyl monomer can be selected from one or more of styrene, ethylene, propylene, vinyl chloride, divinylbenzene monomers and the like.
[0025] Furthermore, the vinyl monomers include styrene and divinylbenzene monomers.
[0026] In the above scheme, the molar ratio of the vinylbenzene monomer, the divinylbenzene monomer and the liquid porogen is 1:0.05-0.85:0.1-0.75.
[0027] In the above scheme, the molar ratio of the total molar amount of (monomer) styrene sulfonate and vinyl monomer (oil phase monomer) in the water phase to the initiator is 1:0.05-0.5.
[0028] In the above scheme, the heating polymerization step includes: polymerization in a 50-100° C. water bath for 1-72 hours at a rotation speed of 200-1000 r / min.
[0029] Preferably, the polymerization time is 1-5h.
[0030] In the above scheme, the Soxhlet extraction step uses toluene or dichloromethane as an extractant, and the extraction time is 2-72 hours.
[0031] Preferably, the polymerization time is 2-10 hours.
[0032] In the above scheme, the purified porous microspheres are vacuum dried for 1-24 hours.
[0033] In the above scheme, the protonation step comprises: adding 0.1-2 mol / L HCl solution for protonation for 1-72 hours.
[0034] The ammonia adsorption material based on bimetallic MOF / resin prepared according to the above scheme has Cu / Co bimetallic MOF as the core and a macroporous adsorption resin wrapped in the outer layer, and the average size of the macropores is 50-200nm; it has a high specific surface area (100-500m 2 / g) and more active sites for ammonia removal.
[0035] The present invention also provides an application of the above-mentioned bimetallic MOF / resin-based ammonia adsorption material for ammonia adsorption, wherein the initial efficiency is more than 70% and the mass adsorption ratio is more than 85%.
[0036] The principle of the present invention is:
[0037] The present invention utilizes a water phase containing styrene sulfonate monomers and Cu / Co bimetallic MOF to react with an oil phase containing vinyl monomers to prepare a Cu / Co bimetallic MOF material; wherein the Cu / Co bimetallic MOF material is dispersed in the oil phase in the synthesis process of styrene resin; since MOF is insoluble in the water phase and the organic phase, during the stirring of the water phase and the oil phase, the organic ligand of MOF is more easily combined with the organic oil phase in the resin synthesis system through non-covalent bond forces, and it is easy to form a triple structure with the bimetallic MOF as the core and having "water-in-oil" and "oil-in-MOF" characteristics (the inner layer is the Cu / Co bimetallic MOF, the middle layer is the oil phase solution, and the outermost layer is the water phase solution), which is helpful for the subsequent synthesis of the resin and improves the porous structure of the resin; as the initiator initiates the free radical polymerization of the organic phase to encapsulate the bimetallic MOF, the bimetallic MOF is effectively encapsulated inside the resin, without the need for traditional subsequent impregnation modification and other means.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1) The present invention first adds the Cu / Co bimetallic MOF to the aqueous phase solution synthesized by the resin, and then mixes and reacts with the organic phase solution synthesized by the resin to prepare a composite ammonia adsorption material, which can significantly shorten the time required for resin synthesis, avoid the risks brought by the use of metal salt impregnation and other processes, and simplify the preparation process;
[0040] 2) The ammonia adsorption material of the present invention has a Cu / Co bimetallic MOF as the core and a macroporous adsorption resin wrapped in the outer layer, has a high specific surface area and a large number of ammonia removal active sites, and has an excellent ammonia removal effect;
[0041] 3) The preparation cost of the ammonia adsorption material of the present invention is low and the cycle is short, which can provide a new idea for the preparation of high-performance ammonia adsorption materials and has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1Infrared spectra of the Cu / Co bimetallic MOF obtained in Example 1 and the ammonia adsorption material based on bimetallic MOF / resin. DETAILED DESCRIPTION
[0043] The following will be a clear and specific description of the technical solutions used in the present invention through examples and comparative examples. The examples and comparative examples are only examples of the present invention, do not represent all examples, and do not limit the scope of the present invention. The embodiments of the present invention, as well as various changes or modifications made by those skilled in the art according to the present invention, these equivalent forms also belong to the scope of protection of the present invention.
[0044] Example 1
[0045] An ammonia adsorption material based on bimetallic MOF / resin, the preparation method of which comprises the following steps:
[0046] 1) Synthesis of Cu / Co bimetallic MOF materials:
[0047] 4g Cu(NO3)2·3H2O, 4g Co(NO3)2·3H2O and 4.8g H3BTC were weighed respectively, added into a mixed solvent consisting of 17ml anhydrous ethanol, 17ml DMF and 17ml deionized water, and ultrasonicated for 30min to obtain a purple solution. The mixed solution was then divided into a reactor, sealed and placed in an oven, heated to 85°C at a heating frequency of 0.5°C / min and maintained for 20h before naturally cooling to room temperature. The obtained product was separated from the solution by filtration, washed with anhydrous ethanol several times, and dried to obtain a Cu / Co bimetallic MOF material.
[0048] 2) Synthesis of Cu / Co bimetallic MOF polystyrene sulfonated resin composite adsorbent material:
[0049] Add 91 ml of deionized water, 5 g of sodium styrene sulfonate and 2 g of azobisisopropyl nitrile, and 0.2 g of Cu / Co bimetallic MOF material into a three-necked flask, and ultrasonically disperse for 30 min to prepare an aqueous solution;
[0050] 50 ml of monomer styrene, 50 ml of monomer divinylbenzene, and 10 ml of porogen toluene were magnetically stirred to obtain an organic phase solution;
[0051] The aqueous solution and the organic solution were mixed in a volume ratio of 3:1 and transferred to the reactor. The stirring speed was set at 400 r·min. -1, polymerized in a water bath at 70°C for 2h; after the reaction, the product was filtered and then washed 2 to 3 times with distilled water, acetone, ethanol and other solvents to remove unreacted monomers and soluble impurities such as stabilizers; extracted with toluene or dichloromethane in a Soxhlet extractor for 8h to remove porogens and organic impurities to form a porous structure, and then washed with methanol and distilled water to fix the porous structure; the purified porous microspheres were vacuum dried for 4h; the obtained sample was placed in a 1mol / LHCl solution for protonation treatment for 24h to obtain a Cu / Co bimetallic MOF / styrene styrene sulfonated resin composite adsorbent material.
[0052] Example 2
[0053] An ammonia adsorption material based on bimetallic MOF / resin, the preparation method of which is roughly the same as that of Example 1, except that the addition amounts of some substances in the synthesis of the sulfonated resin organic phase are different, specifically: the addition amount of Cu / Co bimetallic MOF is 0.25g, the addition amount of styrene is 75ml, and the addition amount of divinylbenzene is 25ml.
[0054] Example 3
[0055] An ammonia adsorption material based on bimetallic MOF / resin, whose preparation method is roughly the same as that of Example 1, except that the addition amounts of some substances in the synthesis of the sulfonated resin organic phase are different, specifically: the addition amount of Cu / Co bimetallic MOF is 0.3g, the addition amount of styrene is 80ml, and the addition amount of divinylbenzene is 20ml.
[0056] Figure 1 The infrared spectra of the Cu / Co bimetallic MOF and the ammonia adsorption material based on the bimetallic MOF / resin obtained in Example 1 are shown in the figure. In the figure, in the wavelength range of 2000-4000, the bimetallic MOF / resin composite material has a similar infrared curve to the sulfonated resin due to the small change of the bimetallic MOF curve. In the wavelength range of 600-2000, the bimetallic MOF / resin is mainly affected by the bimetallic MOF and the sulfonated resin. In the wavelength range of 400-600, the bimetallic MOF / resin is mainly affected by the bimetallic MOF due to the small change of the sulfonated resin.
[0057] Comparative Example 1
[0058] A polystyrene sulfonated resin, the preparation method of which is substantially the same as that of Example 1, except that:
[0059] 1) In step 2), no Cu / Co bimetallic MOF material is introduced;
[0060] 2) In step 2), the water bath polymerization time used is 6 hours and the extraction time is 16 hours.
[0061] Comparative Example 2
[0062] A polystyrene sulfonated resin, whose preparation method is roughly the same as that of Example 1, except that an aqueous phase (not containing a Cu / Co bimetallic MOF material) and an oil phase synthetic resin solution (water bath polymerization time is 6 hours, extraction time is 24 hours) are first mixed, and after the resin synthesis is completed, the Cu / Co bimetallic MOF material is added and stirred at 60°C for 4 hours; and then subsequent washing, drying and protonation treatment are performed.
[0063] The Cu / Co bimetallic MOF / polystyrene sulfonated resin composite adsorbent material obtained in Examples 1 to 3 and the resin-based adsorbent obtained in the comparative example were subjected to BET test and ammonia removal performance test, respectively. The ammonia removal performance test used a domestic AMC chemical filter material test bench, and the test method was operated according to the national standard IOS10121-1: the gas flow rate Q was 15m 3 / h, surface wind speed V f The speed is 2.3m / s, the filter cloth shear diameter is 40mm, the mass is about 5g, the measured gas is ammonia, the temperature is 25℃, the relative humidity is 50%, the upstream concentration of the measured gas is 1ppm, and the test is completed when the downstream concentration is 70% of the upstream concentration; the specific test results are shown in Table 1.
[0064] Table 1 Performance test results of the resin-based adsorbents obtained in Examples 1 to 3 and Comparative Examples
[0065]
[0066]
[0067] The above results indicate that the Cu / Co bimetallic MOF / polystyrene sulfonated resin composite adsorbent material synthesized by the present invention can significantly improve the removal efficiency of ammonia.
[0068] The Cu / Co bimetallic MOF / polystyrene sulfonated resin composite adsorbent material synthesized by the present invention has the following three advantages: on the basis that the acidic ion exchange resin itself can adsorb a portion of ammonia by acid-base neutralization reaction, the Cu / Co bimetallic MOF is further introduced to increase the specific surface area of the resin and increase the ammonia removal active sites, thereby enhancing the ammonia removal performance; the modifier MOF is added during the process of synthesizing the resin, which, on the one hand, avoids subsequent impregnation modification; on the other hand, the modifier MOF particles can be used as the core to promote the acceleration of the resin synthesis process and improve its ammonia adsorption performance, which is beneficial to reducing the preparation cost, shortening the preparation cycle, and helping to achieve industrialization, and is also beneficial to optimizing the porous structure of the resin.
[0069] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an ammonia adsorption material based on bimetallic MOF / resin, characterized in that: The following steps are involved: 1) adding styrene sulfonate, an initiator and a Cu / Co bimetallic MOF material to water, and ultrasonically dispersing the mixture to obtain an aqueous phase solution; and uniformly stirring the vinyl monomer and the liquid porogen to obtain an organic phase solution; 2) The aqueous phase solution and the organic phase solution are mixed, and heated and polymerized under stirring conditions, and the liquid porogen is removed to obtain porous microspheres, which are protonated to obtain the bimetallic MOF / resin-based ammonia adsorption material.
2. The preparation method according to claim 1, characterized in that: The preparation steps of the Cu / Co bimetallic MOF material include: uniformly dispersing copper salt, cobalt salt and organic ligand in a mixed solvent, and then performing heating reaction, cooling, filtering, washing and drying to obtain the Cu / Co bimetallic MOF material.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the copper salt, the cobalt salt and the organic ligand is 1:0.5-2:1-4.
4. The preparation method according to claim 2, characterized in that: The heating reaction step comprises: heating to 50-150° C., keeping the temperature for 1-72 hours, and naturally cooling to room temperature.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the styrene sulfonate, the initiator and the Cu / Co bimetallic MOF material is 1:0.05-0.4:0.01-0.
10.
6. The preparation method according to claim 1, characterized in that: The liquid porogen is one or more of toluene, cyclohexane, n-heptane, linear polystyrene, petroleum ether and dibutyl phthalate.
7. The preparation method according to claim 1, characterized in that: The molar ratio of the vinylbenzene monomer, the divinylbenzene monomer and the liquid porogen is 1:0.05-0.85:0.1-0.
75.
8. The preparation method according to claim 1, characterized in that: The molar ratio of the total molar amount of styrene sulfonate and vinyl monomer in the aqueous phase to the initiator is 1:0.05-0.
5.
9. The preparation method according to claim 1, characterized in that: The temperature used in the heating polymerization step is 50-100° C. and the time is 1-72 hours.
10. The ammonia adsorption material based on bimetallic MOF / resin prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It has a Cu / Co bimetallic MOF as the core and a macroporous adsorption resin as the outer layer. The average size of the macropores is 50-200nm; the specific surface area is 100-500m 2 / g.
Citation Information
Patent Citations
Preparation method of special active carbon for ammonia adsorption
CN104368307A
Ammonia gas adsorbent and preparation method thereof
CN109692662A